PENGARUH MEDIA SOSIAL TERHADAP GAYA HIDUP KONSUMTIF PELAJAR DI KECAMATAN PAMIJAHAN - Liza Maulida Hidayat; Titien Yusnita; Febri Palupi Muslikhah (Fakultas Ilmu Dakwah dan Komunikasi, 2025)
This study aims to determine the influence of social media exposure on the consumptive lifestyle of Muslim students in Pamijahan District. The background of this research is based on the increasing use of social media and digital wallet services among teenagers, which affects consumption patterns and shopping habits. This research employs a quantitative approach using the survey method. The sample consists of 100 respondents who are active students in Pamijahan District. The data analysis technique used is simple linear regression. The results show that social media usage significantly influences the consumptive lifestyle of students, particularly in indicators of impulsive buying and the tendency to prioritize wants over needs.